From Usability to Strategy: Enhancing Higher Education Website Quality through a Data-Driven Evaluation Using WebQual 4.0 and Importance-Performance Analysis - Anita Safitri; Nunik Dwi Kusumawati; Aprillia Nilasari (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2024)
In the era of digital transformation, academic websites play a crucial role in facilitating communication, supporting academic functions, and promoting institutional transparency. This study assesses the quality of a faculty website at a public university in Surabaya, East Java, Indonesia, from the users’ perspective. Utilizing the WebQual 4.0 framework, the research evaluates three key dimensions—usability, information quality, and interaction quality—to determine how effectively the website supports academic activities. To better prioritize areas for improvement, the study incorporates Importance-Performance Analysis (IPA), which helps identify website attributes that are both important to users and currently underperforming. The findings provide an overview of users' perceptions of website effectiveness, highlight aspects that require strategic focus, and offer direction for future enhancements. This research adds to the body of knowledge on digital service quality in higher education by presenting a combined methodological approach that emphasizes user experience. The results offer practical recommendations for university administrators, web developers, and IT teams in optimizing academic websites to better support teaching, learning, and accreditation processes. The study underscores the significance of user-centered design in improving digital services and institutional performance within the higher education context.